Prediction of inorganic crystal framework structures - Part 1: Using a genetic algorithm and an indirect approach to exclusion zones - Woodley, S; Battle, P; Gale, J; Catlow, C (2004)
A genetic algorithm has been used to generate crystal framework structures from the knowledge of only the unit cell dimensions, constituent atoms and by defining exclusion zones-regions within the unit cell from which the constituent atoms are discouraged. The structures of the better candidates produced are relaxed by minimising the lattice energy, which is based on the Born model of a solid. We present details of the implementation within the computational package GULP. Application to generating various microporous silicate framework structures, without imposing any symmetry relations on the ionic positions, is described. The technique developed can be applied generally in generating new feasible framework structures with defined microporous architectures.